Synthesis of TiO₂ and Fe₂O₃-doped TiO₂ for photocatalytic degradation of 2,4-Dichlorophenoxyacetic acid - Razani, Afini (2015)
2,4-Dichlorophenoxyacetic acid (2,4-D), a widely used herbicide for selective control of broadleaf weeds which has been detected as a major contaminant in surface or underground water since its degradation in water is very slow, with half-life ranging from 4 to7 days in most soil types and up to 6 weeks in acidic soils. The TiO2, 0.025%, 0.05% and 0.1% Fe2O3 doped TiO2 were synthesized via co-precipitation method, calcined at 550°C and used as photocatalyst to photodegrade 2,4-D in aqueous solution. The synthesized metal oxides were then characterized by X-Ray Diffractometer (XRD), X-Ray Fluoresence (XRF), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Band Gap, and Brunauer, Emmet and Teller (BET) surface area analysis. All catalysts exhibited spherical anatase TiO2 phase. With the addition of Fe2O3, the surface area, particle size and band gap energy were lower than undoped TiO2. When comparing the photocatalytic activity of TiO2 and Fe2O3 doped TiO2, 0.05% Fe2O3 doped TiO2 was found to give the highest degradation (33.1%). This may attributed to its small particle size (12.67 nm) and low band gap energy (~3.07). Conventional method and Response Surface Methodology (RSM) with a Face-Centred Central Composite Design (FCCCD) was used to optimize the photocatalytic degradation of 2,4-D using 0.05% Fe2O3 doped TiO2 as catalyst. The optimum conditions for photocatalytic degradation of 2,4-D using 0.05% Fe2O3 doped TiO2 were predicted at 10 mg/L of initial concentration of 2,4-D, 1.0 g of mass loading of 0.05% Fe2O3 doped TiO2 and initial 2,4-D pH of 4.0 with a predicted percentage of degradation of 45.24%. The model was validated and the result showed no significant difference between the experimental and the predicted percentage of degradation. The photocatalytic efficiency of the catalyst remained unchanged after the first cycles of photodegradation experiments which indicate the stability of the catalyst until the fifth cycle.